Mutations in the MepRAB efflux system contribute to the in vitro development of tigecycline resistance in Staphylococcus aureus. (September 2020) - Fang, Renchi; Sun, Yao; Dai, Weisi; Zheng, Xiangkuo; Tian, Xuebin; Zhang, Xiucai; Wang, Chong; Cao, Jianming; Zhou, Tieli
Highlights: The evolution of tigecycline resistance in Staphylococcus aureus is mediated by mutations in the MepRAB efflux pump system. This study reports novel mepRAB operon mutation positions in addition to mutation positions that have previously been reported. Resistance to tigecycline in S. aureus is accompanied by a fitness cost in some cases. Abstract: Objective: To characterize the evolutionary pathways of tigecycline (TGC) resistance and alterations in the biological characteristics of hospital-derived Staphylococcus aureus isolates under selective pressure. Methods: Three clinical S. aureus strains and one standard S. aureus strain, ATCC 29213, were used for the in vitro selection of TGC-resistant S. aureus variants with gradient concentrations of TGC. Changes in drug resistance and genetic alterations in resistance-related genes (operon mepRAB and rpsJ ) in mutant strains were determined. The efflux inhibitor assay for MepA and the fitness cost, determined by comparing the growth and virulence of parental and mutant strains, were also investigated. Results: Mutants induced in vitro showed a 64- to 128-fold increase in the minimum inhibitory concentration (MIC) of TGC. Substitution mutations were detected in the transcriptional repressor mepR and the efflux pump gene mepA . A K57M amino acid substitution occurred in the ribosomal S10 protein-encoding gene rpsJ . The MICs of TGC in the final mutants were significantly decreased in the presence of efflux pump inhibitors. It was worth noting that growth was unaffected by TGC resistance selection in vitro, with the exception of one strain, and the MICs of other antibiotics and virulence were also unaffected. Conclusions: The evolution of TGC resistance in S. aureus in vitro is associated with a loss-of-function mutation in the efflux pump transcriptional repressor mepR and a missense mutation in the efflux pump-encoding gene mepA . Our work further validated the resistance mechanisms of S. aureus to TGC and reported previously undiscovered mutations.